Delicious Prose: Reading the Tale of Tobit with Food and Drink, A Commentary. - Naomi S.S. Jacobs (Supplements to the Journal for the Study of Judaism, 2018)
In Delicious Prose: Reading the Tale of Tobit with Food and Drink , Naomi S.S. Jacobs explores how the numerous references to food, drink, and their consumption within The Book of Tobit help tell its story, promote righteous deeds and encourage resistance against a hostile dominant culture. Jacobs' commentary includes up-to-date analyses of issues of translation, text-criticism, source criticism, redaction criticism, and issues of class and gender. Jacobs situates Tobit within a wide range of ancient writings sacred to Jews and Christians as well as writings and customs from the Ancient Near East, Ugarit, Greece, Rome, including a treasure trove of information about ancient foodways and medicine.